2006
DOI: 10.1890/05-0064
|View full text |Cite
|
Sign up to set email alerts
|

Rain Forest Fragmentation and the Proliferation of Successional Trees

Abstract: Abstract. The effects of habitat fragmentation on diverse tropical tree communities are poorly understood. Over a 20-year period we monitored the density of 52 tree species in nine predominantly successional genera (Annona, Bellucia, Cecropia, Croton, Goupia, Jacaranda, Miconia, Pourouma, Vismia) in fragmented and continuous Amazonian forests. We also evaluated the relative importance of soil, topographic, forest dynamic, and landscape variables in explaining the abundance and species composition of successi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
404
3
28

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 399 publications
(454 citation statements)
references
References 83 publications
19
404
3
28
Order By: Relevance
“…In particular (1) population declines and local extinctions in human-modified landscapes predominantly affect particular functional groups (XXXX), (2) edge-affected habitats tend to support distorted tree species assemblages in both taxonomic and functional terms (Laurance et al 2006a;Laurance et al 2006b;Tabarelli et al 2008), (3) these distortions can be readily observed in seedling assemblages (Santo-Silva et al 2013); (3) small forest fragments are becoming increasingly dominated by pioneer species (cf. Pütz et al 2011;Tabarelli et al 2008), (4) some native pioneer species are proliferating at multiple spatial scales , particularly Byrsonima sericea, Bowdichia virgilioides, Cupania oblongifolia and Cupania racemosa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular (1) population declines and local extinctions in human-modified landscapes predominantly affect particular functional groups (XXXX), (2) edge-affected habitats tend to support distorted tree species assemblages in both taxonomic and functional terms (Laurance et al 2006a;Laurance et al 2006b;Tabarelli et al 2008), (3) these distortions can be readily observed in seedling assemblages (Santo-Silva et al 2013); (3) small forest fragments are becoming increasingly dominated by pioneer species (cf. Pütz et al 2011;Tabarelli et al 2008), (4) some native pioneer species are proliferating at multiple spatial scales , particularly Byrsonima sericea, Bowdichia virgilioides, Cupania oblongifolia and Cupania racemosa.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the collapse of the old-growth tree flora and the proliferation of pioneers, particularly short-lived species, have been well documented in Amazonian forest landscapes dominated by both cattle pastures and young secondary forests (Laurance et al 2006b) and open water (Benchimol and Peres 2015). Based on the patterns found here, we also expect that recently fragmented Amazonian forest landscapes will eventually experience a proliferation of long-lived, canopy pioneers, including hardwooded species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The processes that rule edge effects in forest fragments are well understood and reasonably consistent throughout the studies carried out in temperate (WHITNEY;RUNKLE, 1981;PALIK;MURPHY, 1990;MATLACK, 1994;HANSSON, 2000) and tropical rain forests (LOVEJOY et al, 1983;WILSON;CROME, 1989;WILLIAMS-LINERA, 1990a;LAURANCE, 1991;LAURANCE et al, 1998;RODRIGUES, 1998;WILLIAMS-LINERA et al, 1998;LAURANCE et al, 2006). However, edge effect trends found elsewhere may not be directly applicable to tropical dry forests.…”
Section: Introductionmentioning
confidence: 74%
“…Even in the Amazon rain forest, where edge effects were considered formerly as one of the most extensive impacts for biodiversity conservation of forest fragments (LAURANCE, 2000;LAURANCE et al, 2006). PHILLIPS et al (2006) reported the absence of edge effects fragments in rain forests from the Southwestern Peruvian Amazon.…”
Section: Discussionmentioning
confidence: 99%